(untitled) (Medicine Today, 2018)
Rheumatoid arthritis is an autoimmune disease characterized by joint destruction, disability and disability adjusted life years of a patient. Early diagnosis and appropriate treatment may improve outcome. Diseasemodifying anti-rheumatic drugs suppress the disease progression. Recent guidelines advise early and sustained use of disease-modifying anti-rheumatic drugs of which methotrexate (MTX) and sulfasalazine (SSZ) are the most frequently used. Both drugs are effective, cheap, available and well tolerable. Now days MTX and SSZ are used as monotherapy and in combination. Basically the outcomes of two combinations of drugs are multiplicative. One drug promotes the action of the other. In daily practice interactions are often not well studied when using combinations of Disease Modifying Anti-Rheumatic Drugs (DMARDs). The aim of this study is the use of combination of MTX and SSZ is frequently used in the therapy for RA and has been tested in several clinical trials globally. Medicine Today 2018 Vol.30(2): 89-94